Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Kantor Camat Sukasada - Kadek Rani; Gede Widiadnyana Pasek (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This research was conducted to see the impact of motivation and work environment on employee performance at the Sukasada District Office. The objectives of the research include: 1) to see the magnitude of the impact of work motivation on employee performance at the Sukasada Sub-District Office and 2) to see the magnitude of the environmental impact on employee performance at the Sukasada Sub-District Office. The research method used is a quantitative approach. The research location is the Sukasada Sub-district Office. The sample selection method applied was all employees of the Sukasada Sub-district Office, namely 56 people. The data analysis technique used was classical assumption test, multiple linear regression and t-test. The following are the research findings: 1) Work motivation has a positive and significant impact on the performance of the Sukasada Sub-District Office employees. 2) The work environment has a positive and significant impact on the Sukasada Sub-District Office employee performance. The impact of this research is that there is a workspace supervisor so that the obligations of employees are made properly and it is hoped that the existence of good work motivation can trigger the desire and enthusiasm of employees to carry out their duties in the organization and in the company. Keywords: Motivation, Work Environment, Employee Performance